Respon Petani Terhadap Penggunaan Pupuk Organik pada Budidaya Padi Sawah di Poktan Tani Makmur II Mojoayu Kecamatan Plemahan Kabupaten Kediri - Purbasiswanta, Johan Syahputra; Artini, Widi; Sutiknjo, Tutut Dwi; Pamujiati, Agustia Dwi (Universitas Kadiri, 2024)
This study examines farmers' response to using organic fertilizers in paddy cultivation at the Makmur II Mojoayu Farmers Group, Plemahan District, Kediri Regency. The background of this research was the limited stock of subsidized fertilizers and the high prices of chemical fertilizers, which have led farmers to turn to organic fertilizers as an alternative solution. The research method used was quantitative, with survey techniques and questionnaires as data collection instruments. A total of 30 respondents from the Makmur II Farmers Group were involved in this study. Analyzing internal factors such as age, formal education, income, and land size shows a positive relationship with farmers' knowledge, attitudes, and skills in using organic fertilizers. External factors such as expected benefits and non-formal education also positively affect the farmers' responses. The results of this study emphasize the importance of considering these factors in efforts to increase the adoption of organic fertilizers among farmers. This research provides insights for policymakers and practitioners in the agricultural field to design more relevant and effective programs and interventions to enhance the use of organic fertilizers. It highlights the importance of non-formal education in improving farmers' skills and knowledge. Penelitian ini mengkaji respon petani terhadap penggunaan pupuk organik dalam budidaya padi sawah di Kelompok Tani Makmur II Mojoayu, Kecamatan Plemahan, Kabupaten Kediri. Latar belakang penelitian ini adalah keterbatasan stok pupuk subsidi dan tingginya harga pupuk kimia, yang mendorong petani untuk beralih ke pupuk organik sebagai alternatif. Metode penelitian yang digunakan adalah pendekatan kuantitatif dengan teknik survei dan kuesioner sebagai alat pengumpulan data. Sebanyak 30 responden dari Kelompok Tani Makmur II dilibatkan dalam penelitian ini. Analisis faktor internal seperti usia, pendidikan formal, pendapatan, dan besar lahan menunjukkan hubungan positif dengan pengetahuan, sikap, dan keterampilan petani dalam penggunaan pupuk organik. Faktor eksternal seperti manfaat yang diharapkan dan pendidikan non-formal juga menunjukkan hubungan positif dengan respon petani. Hasil penelitian ini menekankan pentingnya mempertimbangkan faktor-faktor tersebut dalam upaya meningkatkan adopsi pupuk organik di kalangan petani. Penelitian ini memberikan wawasan bagi pengambil kebijakan dan praktisi di bidang pertanian untuk merancang program dan intervensi yang lebih relevan dan efektif dalam meningkatkan penggunaan pupuk organik, serta menunjukkan pentingnya pendidikan non-formal dalam meningkatkan keterampilan dan pengetahuan petani.